The mediating role of illness perception in the relationship between psychological hardiness and the health status of covid-19 (coronavirus disease) survived patients - Sajjad Rezaei; Mohammad Hoseini nia; Mozhgan Vakilian (Health Psychology Research)
This study investigates whether the illness perception mediates the relationship between psychological hardiness and the health status of Covid-19 survived patients. In a cross-sectional study, 205 Covid-19 were selected by purposive sampling from Qom (the first coronavirus epidemiological site in Iran) and responded to Abridged Hardiness Scale (AHS) and Brief Illness Perception Questionnaire (Brief IPQ) and Patient Health Questionnaire (PHQ-9). Results: The results of correlation showed that the relationship between AHS scores with PHQ-9 (P\<0.01) and Brief IPQ (P\<0.01) was negative and significant. The relationship between Brief IPQ and PHQ-9 scores was also positive and significant (P\<0.01). The proposed mediating model had a relatively good fit. However, a better fit was achieved by releasing several covariance errors and explained 47% of the PHQ-9 scores (χ^2^/df=2.46, RMSEA=0.075, CFI=0.950, PCFI=0.689, IFI=0.953, GFI=0.964). The Bootstrap analysis showed that Brief IPQ scores significantly mediated the relationship between AHS and PHQ-9 scores (95% CI: -0.073 to -0.002). The findings suggest a more negative perception of perceptions Covid-19 disease is associated with lower levels of patient health. As a mediating variable, it prevents the positive effects of psychological hardiness on improving patients' health. The application of these findings has been discussed.